ANALYSIS OF THE RESULTS OF ENDOSCOPIC STENT IMPLANTATION IN MALIGNANT EXTRINSIC ESOPHAGEAL СOMPRESSIONS AND ESOPHAGEAL ANASTOMOSES - A. I. Ivanov; V. A. Popov; M. V. Burmistrov (Сибирский онкологический журнал, 2021)
Background. Malignant dysphagia caused by the extrinsic compression of the esophagus and esophageal anastomoses is a rare complication of malignant neoplasms. Studies on the safety and efficacy of esophageal stenting for extra-organ esophageal compression have contradictory results. The aim of the study was to analyze the life expectancy and complications after stenting in patients with malignant extra-organ compression of the esophagus and esophageal anastomoses. Material and Methods. From 2011 to 2019, 19 patients with extrinsic compression of the esophagus and esophageal anastomoses caused by malignant neoplasms underwent ultrasound-guided implantation of self-expandable metallic stents. Results. No complications were observed during stent implantation procedure. The mean dysphagia score decreased by 1.9 points. Short-and long-term complications, such as stent migration, profuse esophageal bleeding with lethal outcome, dysphagia relapse, tracheo-esophageal fistula, pronounced and granulation growth causing recurrent dysphagia, were observed in 5 patients. The median survival time was 55.9 days. Conclusion. placement of metal stents in patients with malignant dysphagia due to extrinsic esophageal compression was shown to be safe and effective in relieving the symptoms of dysphagia.